2015
DOI: 10.1016/j.foodchem.2014.09.084
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation enhances the content of bioactive compounds in kidney bean extracts

Abstract: The influence of solid (SSF) or liquid state fermentation (LSF) for 48 and 96 h on the production of water soluble extracts from kidney beans was investigated. SSF was carried out by Bacillus subtilis, whilst LSF was performed either by natural fermentation (NF) or by Lactobacillus plantarum strain (LPF). SSF extracts showed high soluble phenolic compound content (31-36 mg/g) and antioxidant activity (508-541 μg trolox equivalents/g), whilst LSF extracts exhibited potential antihypertensive activity due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
105
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(123 citation statements)
references
References 45 publications
12
105
0
6
Order By: Relevance
“…Surprisingly, same authors reported the synthesis of tyrosol and an increase in free quercetin due to the hydrolysis of quercetin glucosides [49]. Nevertheless, such documented changes have been atributed to the action of glycosidases and esterases from LABs releasing free aglycones, phenolic acids, hydroxyl-cinnamic acids, and less esteriied proanthocyanidins and the transformation of bound to free phenolics during fermentation [49,55,[70][71][72][73].…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…Surprisingly, same authors reported the synthesis of tyrosol and an increase in free quercetin due to the hydrolysis of quercetin glucosides [49]. Nevertheless, such documented changes have been atributed to the action of glycosidases and esterases from LABs releasing free aglycones, phenolic acids, hydroxyl-cinnamic acids, and less esteriied proanthocyanidins and the transformation of bound to free phenolics during fermentation [49,55,[70][71][72][73].…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…Lactic acid bacteria have also been traditionally used in legume fermentation since they are naturally present in legume grains. The lactic acid fermentation of legumes with Lactobacillus can enhance the production of bioactive compounds, providing health benefits beyond basic nutrition [16]. Fermentation can also result in the reduction of anti-nutritional components such as protease inhibitors, phytic acid, urease, and oxalic acids [14].…”
Section: Soybeansmentioning
confidence: 99%
“…The extraction of antioxidant compounds from bean samples were done as described by Limomon et al [9], with slight modifications. To 0.500 g of sample, 5 mL of acidified methanol (HCl : methanol : water, 1 : 80 : 20, V/V/V) was added in 10 mL centrifuge tubes and shaken at room temperature for 2 h using a horizontal rotary shaker (RKVSD, ART Inc., Laurel, MD, USA).…”
Section: Determination Of Oxygen Radical Absorbance Capacitymentioning
confidence: 99%